BASIC BASKETBALL TECHNIQUE ABILITY FOR PHYSICAL EDUCATION STUDENTS STKIP PGRI JOMBANG - Arnaz Anggoro Saputro (Universitas Majalengka, 2022)
2020 is the first year of selection for new student admissions for those who choose a study program in the arts and/or sports. The purpose of this study was to determine the basic technical ability of basketball in physical education students. This study is a descriptive study with a sample of 130 students aged 17-21 years. The instrument used was a passing test to the wall with a distance of 3 meters for 30 seconds, a shooting test for 30 seconds, and a dribbling test with a zig zag. Data were analyzed using descriptive statistical techniques. From the results of the study obtained information that the average basic technical ability of students' basketball is in the sufficient category based on the value reference assessment (PAN). There needs to be a comparison between student admissions through other channels so that it can be seen the differences in student abilities in each admission path based on the sport being taught.